A two phase local study, comparing liquid-based cytology to the conventional cervical pap smear - Van Rensburg, Jacobus A (Department of Obstetrics and Gynaecology, 2024)
Cancer of the cervix is the most common cancer in women in developing countries and constitutes 33% of all malignant tumours in black women in South Africa. Four out of every 5 cases of cervical cancer occur in developing countries, where only 5% of women receive a repeat PAP smear within a five year period. The lifetime risk for the development of cervical cancer in black South African women is an estimated 1 :26 compared to 1 :83 for white South African women, the majority of whom have been screened. The age standardised incidence rates (ASIR) of cervical cancer are expressed as the number of cases of cervical cancer per 100 000 women in the population. In 1992, the South African pathology-based Cancer registry reported the ASIR of cervical cancer as 35/100 000 for black women and 12/100 000 for white women. 11: is believed that many women who die of cervical cancer in developing countries do not reach hospitals and do not have their disease diagnosed histologically, so the rates quoted are probably an underestimate of the true incidence. (See Table 1).